2018
DOI: 10.3168/jds.2017-13941
|View full text |Cite
|
Sign up to set email alerts
|

A canonical discriminant analysis to study the association between milk fatty acids of ruminal origin and milk fat depression in dairy cows

Abstract: Although milk fat depression (MFD) has been observed and described since the beginning of the last century, all the molecular and biochemical mechanisms involved are still not completely understood. Some fatty acids (FA) originating during rumen biohydrogenation have been proposed as causative elements of MFD. However, contradictory results were obtained when studying the effect of single FA on MFD. An alternative could be the simultaneous evaluation of the effect of many FA using a multivariate approach. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 69 publications
5
22
1
3
Order By: Relevance
“…Diet composition is the main factor that can cause shifts in the microbial diversity of the rumen [ 40 ] with subsequent changes in milk FAs. This is because individual categories of bacteria have different lipid metabolism and thus produce higher proportions of specific FAs, such as odd-chain FAs (liquid phase bacteria), C18:1 trans isomers (bacteria firmly attached to feed particles), or branched-chain FAs (bacteria loosely attached to feed particles) [ 41 ]. Recent research has demonstrated that a shift in rumen microbiota followed by changes to the milk FA profile can occur in response to high-starch diets [ 42 ], oil supplementation [ 43 ], changes in forage:concentrate ratio [ 44 ], or a switch from total mixed ration (TMR) to pasture [ 45 ], as also documented in Table 1 comparing pasture-based and silage-based feeding systems.…”
Section: Effects Of Nutrition and Metabolic Aspects Of Cattle On Mmentioning
confidence: 99%
“…Diet composition is the main factor that can cause shifts in the microbial diversity of the rumen [ 40 ] with subsequent changes in milk FAs. This is because individual categories of bacteria have different lipid metabolism and thus produce higher proportions of specific FAs, such as odd-chain FAs (liquid phase bacteria), C18:1 trans isomers (bacteria firmly attached to feed particles), or branched-chain FAs (bacteria loosely attached to feed particles) [ 41 ]. Recent research has demonstrated that a shift in rumen microbiota followed by changes to the milk FA profile can occur in response to high-starch diets [ 42 ], oil supplementation [ 43 ], changes in forage:concentrate ratio [ 44 ], or a switch from total mixed ration (TMR) to pasture [ 45 ], as also documented in Table 1 comparing pasture-based and silage-based feeding systems.…”
Section: Effects Of Nutrition and Metabolic Aspects Of Cattle On Mmentioning
confidence: 99%
“…Studies have shown that the occurrence of MFD is closely related to the intermediates of unsaturated fatty acid biohydrogenation in the rumen, including trans-10, cis-12 conjugated linoleic acid (CLA), cis-10, trans-12 CLA, trans-9, cis-11 CLA, trans-10 C18:1, etc. [9][10][11]. MFD-related intermediates, such as increased trans-10, cis-12 CLA, could inhibit mammary uptake and de novo synthesis of fatty acids, consequently decreasing milk fat production [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…ЛДА виявився ефективним інструментом для визначення головних відмінностей між коровами м'ясних та молочних порід із нормальним отеленням та тварин, які мали проблеми під час отелення (дистоція), що дало змогу прогнозування виникнення можливих ускладнень на підставі низки ознак корови (Morrison et al, 1985;Basarab et al, 1993;Zaborski et al, 2018). Використовується ЛДА й для визначення фальсифікації молока (Conte et al, 2018) чи м'яса (Boyaci et al, 2014).…”
Section: вступunclassified